Double whammy- acute splenic sequestration crisis in patient with aplastic crisis due to acute parvovirus infection - Parminder S. Minhas; Jaspreet K. Virdi; Rajeshkumar Patel (Greater Baltimore Medical Center, 2017)
Splenic dysfunction is a major feature of sickle cell disease (SCD) and can manifest as acute splenic sequestration crisis (ASSC), which is the earliest life-threatening complication seen in patients with SCD. Aplastic crisis is another potentially deadly complication of sickle cell disease that develops when erythrocyte production temporarily drops. Infection with parvovirus B-19 frequently causes aplastic crises. These two complications are known to be mutually exclusive due to their classic presentation signs and symptoms but there have been few cases where a patient can have concomitant presentation of both phenomena, which can result in a fatal outcome. These few cases force us to rethink the etiology and subsequent management guidelines of these complications. We present to you a case of an unfortunate 23-year-old female who had both complications occurring at the same time, resulting in death.